Pengaruh Suku Bunga dan Nilai Tukar Rupiah Terhadap Pertumbuhan Ekonomi dan Nilai Ekspor di Indonesia - Sri Wigati; Abdul Wahid (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2022)
International trade is a tool in increasing the country's economic growth. This research intends to conduct an analysis of the open rate and the exchange rate on Indonesia's economic growth. An analysis was also conducted on the impact of interest rates, exchange rates and economic growth on the value of Indonesia's exports. Efforts to obtain scientific results require the use of scientific methods where in this research path analysis is used by utilizing the SPSS program. The results obtained are interest rates and exchange rates have a direct impact in the form of a negative impact on Indonesia's economic growth. The impact of interest rates is not significant but positive. while Indonesia's economic growth has a positive and significant impact on exports. Economic growth also mediates the effect of interest rates and exchange rates on the value of Indonesia's exports.